MENJAGA TOLERANSI BERAGAMA DENGAN TEOLOGI ISLAM - Nurfi, Indah; Batubara, Chuzaimah (UIN Sumatera Utara, 2021)
Tolerance in the sense of brotherhood refers to respect and acceptance of one another. Islam is a belief revealed by Allah through His Messenger Muhammad SAW as a mercy to the universe, rahmatan lil 'alamin, and applies to all humans on earth as a moral guide for humans both in the East and in the West. Nevertheless, despite the fact that there are many other religions that individuals profess today, these widely held beliefs continue to acknowledge and respect each other's existence and the fact that Allah has honestly given everyone the freedom to follow any religion. . which they choose. The main principle of Islam is to provide a calm and pleasant atmosphere for human existence as a blessing for the existence of the universe. Freedom of religion, according to the Qur'an, is the absence of deficiency in practicing one's religion and the inability to coerce non-Muslims into Islam. Both Muslims and non-Muslims can propagate their own religion both within and outside their own social circle, and defend it from criticism or harm.Keywords: Islam, Tolerance, Establishing harmony